Program Bunda Mandiri Sejahtera (BISA) Sebagai Program Pemberdayaan Ekonomi - Fidia Larasati; Saeful Anwar (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
This research aims to analyze the Bunda Mandiri Sejahtera (BISA) program through the implementation of the program and to find out the results of economic empowerment of orphans through the Bunda Mandiri Sejahtera (BISA) program. This research is qualitative research using descriptive methods. Based on the results of the research shows that: first, the Bunda Mandiri Sejahtera (BISA) program is a small group-based widow empowerment program by providing Islamic religious guidance, parenting and economic empowerment. Second, the implementation of the Bunda Mandiri Sejahtera (BISA) program through several stages starting with regional surveys, recruitment of members, then coaching, providing capital assistance and business implementation and monitoring. Third, the results of economic empowerment of orphan mothers Bunda Mandiri Sejahtera (BISA) program not only make orphans can be independent financially or economically but also morally and religiously.